Pelatihan Pengelolaan Pelaporan Keuangan di Wartek Putra Bahari dan Warmindo Ar Rahman - Yohanes Rivaldo Saru Papa; Endang Sri Utami (Universitas Maritim AMNI Semarang, 2025)
At Wartek Putra Bahari and Warmindo Ar Rahman, this training program aims to improve financial reporting management skills. MSME owners will get complete guidance on interesting financial details, ensuring accuracy and consistency with applicable guidelines. The purpose of this service is to provide the knowledge and skills needed by every MSME business actor who is responsible for financial reporting so that financial records remain accurate and transparent. Through a combination of hypothetical learning and thorough preparation, MSME owners will gain an important understanding of the interaction of financial disclosure, empowerment carried out in financial administration at Wartek Putra Bahari and Warmindo Ar Rahman